4‐(Dimethylamino)Pyridinium Azide in Protic Ionic Liquid Media as a Stable Equivalent of Hydrazoic Acid. Issue 14 (30th June 2022) - Andreev, Ivan A.; Boichenko, Maksim A.; Ratmanova, Nina K.; Ivanova, Olga A.; Levina, Irina I.; Khrustalev, Victor N.; Sedov, Igor A.; Trushkov, Igor V.
Abstract: We report a procedure for the multigram synthesis of 4‐(dimethylamino)pyridinium azide, a stable, non‐explosive, low‐hygroscopic source of azide ion soluble in both protic and aprotic organic solvents. In protic ionic liquid media this reagent was shown to serve as a safer equivalent of toxic and unstable hydrazoic acid. The synthetic utility of this system was demonstrated using donor‐acceptor cyclopropane ring opening as a model process. General procedures furnishing a variety of dialkyl (2‐azido‐2‐arylethyl)malonates or 4‐azido‐4‐arylbutyrates, depending on the protic ionic liquid applied, were elaborated. The conversion times for studied donor‐acceptor cyclopropanes were established providing the relative reactivity sequence. The application of 4‐(dimethylamino)pyridinium azide for a conventional nucleophilic substitution, oxirane ring opening, (3+2)‐cycloaddition to (thio)cyano group as well as their combinations realized as telescopic synthesis was also demonstrated. Abstract :